STUDY OF REFUGIA AND VARIETIES TO REDUCE THE INTENSITY OF SPODOPTERA FRUGIPERDA AND INCREASE PREDATORS OF SWEET CORN PESTS - Namsen Sartonedi S Girsang; Asmanizar; Noverina Chaniago (RADJA PUBLIKA, 2025)
The research was conducted at the Experimental Field of the Faculty of Agriculture, University of Islam Sumatera Utara, Jln. Karya Wisata, Gedung Johor, Medan Johor District, Medan City, North Sumatra Province, at an altitude of approximately 25 metres above sea level, with flat topography. This research was conducted from January to March 2025. S. frugiferda is an important pest on corn plants that can cause losses with an attack intensity of up to 80%. The purpose of this research was to determine the effect of refugia plants and corn varieties on S. frugiferda attacks and the number of pest predators. This study used a split-plot design with two treatment factors, namely refugia plants Turnera subulata (B1), Tagetes erecta (B2), No Refugia (B0), and treatments of Pertiwi variety (V1) and Advanta Madu 59 variety (V2). The results showed that the Turnera subulata refugia plant and the Advanta Madu 59 variety produced lower S. frugiferda pest attacks and higher numbers of pest predators, although this was not statistically significant.